Quality of life of patients with facial prosthesis - Douglas Rangel-Goulart; Eder Alberto Sigua-Rodriguez; Natalia Alvarez-Pinzón; Aline Úrsula Rocha-Fernandes; Elizabeth Queiroz (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Objective: evaluate the quality of life and self-esteem of patients with facial deformities in the nasal, oculo-palpebral, and auricular areas using bucco-maxillofacial prostheses. Methods: descriptive study in users of facial prostheses who were rehabilitated at the dental clinic of the University Hospital of Brasilia in the period 2004–2011. The average age of patients was 63.8 years. The data collection instruments were the SF-36 questionnaire and a survey containing the Rosenberg Self-Esteem/EPM scale. Results: skin cancer was the predominant etiologic factor (n = 4). Most patients think that their deformity is visible to some degree (n = 4) and for three of them this fact impacts negatively the frequency to visit public places. The self-esteem scale yielded an average score of 4.6. In evaluating the quality of life by means of the SF-36 questionnaire, there were scores like pain (46.67) and emotional aspects (33.33). Conclusion: the results demonstrate the importance of conducting systematic follow-ups to these patients. Most surveyed patients experienced an increase in quality of life, as well as a higher self-esteem, which can be explained by the functionality and aesthetics offered by the prosthesis. This study is part of an assessment program conducted with the intention of structuring multidisciplinary rehabilitation programs.